Pemberian Short Wave Diathermy (SWD) Kombinasi Streching Exercise Mengurangi Nyeri Leher Myogenik pada Petugas Rekam Medis RSI Aisyiyah Malang - Wiwin Prasetyo; Achmad Abdullah; Rachma Putri Kasimbara; Yohanes Deo Fau; Angria Pradita (FORIKES, 2021)
Neck pain is a musculoskeletal condition with a high prevalence that can affect the physical, social, and psychological aspects of individuals, most commonly found in productive age due to static work positions for a long time. One of the physiotherapy interventions is the provision of shortwave diathermy and stretching. Where shortwave diathermy has the effect of increasing collagen, inhibiting sympathetic activity and increasing tissue viscoelasticity and stretching is intended to reduce muscle pain and increase neck functional ability in patients with neck pain. This study was conducted to determine the effectiveness of shortwave diathermy and stretching in reducing pain in the medical record officer of RSI Aisyiyah. A quasi-experimental study with a pre-post one group design on a medical record population of 50 people with random sampling found 30 samples, using a visual analogue scale. The data processing of this study used the Wilcoxon test, and the results of the study obtained that the pre-post median value of the intervention was 6.00-2.00 with a P value of 0.00 (<0.005). This study revealed that there was an effect of changes in pain values on the administration of SWD combination stretching exercise.Keywords: shortwave diathermy; stretching; neck painABSTRAKNyeri leher merupakan kondisi muskuloskeletal dengan prevalensi tinggi yang dapat mempengaruhi aspek fisik, sosial, dan psikologis individu paling banyak ditemukan pada usia produktif akibat posisi kerja statis dalam waktu yang lama. Salah satu intervensi Fisioterapi adalah pemberian short wave diathermi dan stretching. Dimana short wave diathermy memiliki yang memiIiki efek meningkatkan kolagen, menghambat aktifitas simpatik serta meningkatkan viskoelastis sifat jaringan dan stretching dimaksudkan pada penguIuran otot dapat menurunkan nyeri dan meningkatkan kemampuan fungsionaI leher pada penderita nyeri tengkuk. Studi ini dilakukan untuk mengetahui efektifitas short wave diathermi dan stretching dalam menurunkan nyeri pada petugas rekam medis RSI Aisyiyah. Studi quasi eksperimen dengan desain pre-post one group pada populasi rekam medis 50 orang dengan penarikan sampel secara acak ditemukan 30 sampel, menggunakan alat ukur visual analogue scale. Pengolahan data studi ini menggunakan uji Wilcoxon, dan diperoleh hasil penelitian nilai median pre-post pemberian intervensi sebanyak 6.00-2.00 dengan nilai P 0.00 (<0.005). Studi ini mengungkapkan bahwa, terdapat pengaruh perubahan nilai nyeri pada pemberian SWD kombinasi stretching exercise.Kata kunci: shortwave diathermy; stretching; nyeri leher